Lithium Dendrite Suppression Enabled by Hybrid Separators and Coatings - Dienemann, Lara. (Tufts University. Tisch Library., 2023)
Thesis (Ph.D.)--Tufts University, 2023.; Submitted to the Dept. of Mechanical Engineering.; Advisors: Matthew Panzer, and Marc Hodes.; Committee: Iryna Zenyuk, and Matthew McDowell.; Keywords: Energy, Materials Science, and Engineering.